Implementation of Provision of Assimilation in the Time of Covid-19 for Prisoners - Dwi Seno Wijanarko (Green Publisher Indonesia, 2022)
A criminal act committed by a person does not eliminate his human dignity, so that his position as a prisoner does not prevent him from getting guaranteed protection and fulfillment of human rights. This provision then animates the existence of a correctional system with a set of accompanying legal instruments, including a coaching system which is embodied in the form of an assimilation program. As part of the prisoner development system, the implementation of assimilation has faced challenges during the COVID-19 pandemic. Departing from the description above, the researcher intends to conduct research related to the implementation of assimilation during the COVID-19 pandemic by placing the research locus in Cipinang Class I Prison. The objectives to be achieved in this research are: 1) Knowing the process of providing assimilation for prisoners in Cipinang Class I Correctional Institution; 2) Knowing the impact resulting from the provision of assimilation for prisoners in the Cipinang Class I Correctional Institution. The type of research used in this study is empirical legal research which bases research on findings in the field, so the approach used in this research is a sociological juridical approach. The results of this study are first, the implementation of assimilation in Cipinang Class 1 Prison is based on the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020. Based on this legal source, Cipinang Class 1 Prison has given as many as 533 assimilation rights to prisoners. Second, the provision of assimilation carried out during the Covid-19 pandemic subsequently brought positive and negative impacts at the same time